Environmental taxation and the double-dividend: The role of factor substitution and capital mobility - Ary Lans Bovenberg; Ruud A. de Mooij (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper deals with the so-called 'double-dividend' of an environmental tax reform. We find that, in a model with only labor and a polluting input as factors of production, society faces a trade-off between internalizing environmental externalities and raising revenues in the least distortionary way. However, if either fixed or mobile capital enters the production structure, an ecological tax reform may render the tax structure more efficient from a non-environmental point of view, thereby raising not only environmental quality but also private incomes.
Keywords: 330; Umweltabgabe; Externer Effekt; Faktorsubstitution; Kapitalmobilität; Optimale Besteuerung; Theorie